Peningkatan Kemampuan Memahami Sistem Regulasi Manusia Pada Pelajaran Biologi Melalui Metode Diskusi Pada Siswa Kelas XI SMA N 1 Tapung - Sukarsih, Siti (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
Teachers in providing learning materials to students need a variety of learning methods. Learning methods are implemented in order to achieve the learning objectives that have become targets in the lesson plans are prepared. As the subject of Biology for the students of grade XI SMA N 1 Tapung on the material of the human regulation system, the teacher feels that it is still not optimal in giving the material, it is presumably because the old system with the lecture method is still not effective. Discussion methods are attempted to replace previous methods. Using action research method that is classroom action research and also use student of class XI as research object and appraisal system which done by qualitative hence obtained research result of acquisition of learning result through discussion of research cycle I, II and III about result of biology study material of human regulation system and its implementation, through the discussion learning model obtained data for mastery 75 continue to experience improvement in learning outcomes. Keywords: The ability to understand, the human regulatory system, the method of discussion